2020
DOI: 10.1038/s41598-019-57178-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Coefficient of Variation in Total Fecal Bile Acids Precedes Diagnosis of Necrotizing Enterocolitis

Abstract: Accumulation of bile acids (BAs) may mediate development of necrotizing enterocolitis (NEC). Serial fecal samples were collected from premature infants with birth weight (BW) ≤ 1800 g, estimated gestational age (EGA) ≤ 32 weeks, and <30 days old prior to initiation of enteral feeding. Nine infants that developed Bell's Stage ≥ II NEC were matched with control infants based on BW, EGA, day of life (DOL) enteral feeding was initiated and DOL of the first sample. From each subject, five samples matched by DOL col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Comparisons of fecal excretion of bile salts with diet have demonstrated highest BA loss in infants fed a high LCPUFA, soy-based formula, lower loss in infants fed bovine-based formula, and lowest loss in infants fed exclusively HM [ 194 ]. Alternatively, Halpern et al demonstrated, if high levels of bile acids are not excreted through the feces, but rather taken up by ileal enterocytes, they may be inappropriately retained within the intestinal epithelium, resulting in mucosal damage in rodents very similar to that seen in human NEC [ 195 , 196 , 197 ].…”
Section: Physiological Consequences Of and Influences On Differementioning
confidence: 99%
“…Comparisons of fecal excretion of bile salts with diet have demonstrated highest BA loss in infants fed a high LCPUFA, soy-based formula, lower loss in infants fed bovine-based formula, and lowest loss in infants fed exclusively HM [ 194 ]. Alternatively, Halpern et al demonstrated, if high levels of bile acids are not excreted through the feces, but rather taken up by ileal enterocytes, they may be inappropriately retained within the intestinal epithelium, resulting in mucosal damage in rodents very similar to that seen in human NEC [ 195 , 196 , 197 ].…”
Section: Physiological Consequences Of and Influences On Differementioning
confidence: 99%
“…It has been reported that DCA is closely related to NEC by regulating cell proliferation or the BA transporter 27,28 . Similarly, LCA has been found to be elevated in intestinal bile salts from patients with NEC 29 . However, the role and mechanisms of LCA in NEC remains clear.…”
Section: Introductionmentioning
confidence: 99%
“…In chapter 5, total ileal BA concentrations remained unchanged at different time points after IA LPS administration. In line, in a more recent study in which NEC infants were compared to matched controls, no differences in total fecal BAs nor differences in BA species were found (64). However, in the month prior to NEC diagnosis, a difference in the mean coefficient of variation of total BAs was detected when compared to controls (64).…”
Section: The Effect Of Chorioamnionitis On the Liver And Enterohepatic Circulation Of Bile Acidsmentioning
confidence: 58%
“…However, in the month prior to NEC diagnosis, a difference in the mean coefficient of variation of total BAs was detected when compared to controls (64). This latter finding indicates that fluctuations in fecal BA levels were measured, which suggests that the neonatal ileum may be especially sensitive to pulsatile exposure to BAs in the first month, potentially contributing to NEC development (64).…”
Section: The Effect Of Chorioamnionitis On the Liver And Enterohepatic Circulation Of Bile Acidsmentioning
confidence: 96%
See 1 more Smart Citation